The production of gendered knowledge of war : women and epistemic power - Björkdahl, Annika; Selimovic, Johanna Mannergren (Routledge advances in feminist peace research, 2025)
"This edited volume critically investigates women's knowledge about war and explores the epistemic agency of women in a range of contemporary settings across the globe. Women are deeply affected by war, participate in war and resist war. At the same time, knowledge production often ignores and marginalizes women's experiences and gendered ways of knowing war. From Colombia to Israel and Palestine, Liberia, Mali, Myanmar, Nepal, North America, Northern Iraq and Ukraine, the chapters in this book illuminate gendered knowledge production in and about different conflict-affected sites. By taking the embodied and narrative epistemic agency of local 'knowers' seriously, new insights are thereby presented about the role women play in producing knowledge about war. The book proposes new theoretical vantage points in order to understand how epistemic power and epistemic violence are closely related. Bringing the topic of knowledge production into the so-called 'Women, Peace and Security' (WPS) agenda, it analyses how knowledge of the gendered nature of war and security is produced and circulated, and argues that the WPS agenda is a system of knowledge with its own omissions and silences. By theorizing gendered knowledge production and amplifying the voices of women as epistemic agents, this book advances scholarship on gender and war. This book will be of much interest to students of feminist studies, peace studies, war and conflict studies and International Relations"-- Provided by publisher.